(untitled) (INTERNATIONAL JOURNAL OF RECENTLY SCIENTIFIC RESEARCHER’S THEORY, 2024)
This article discusses the methodology of teaching the mother tongue. The main methods used in the teaching process, didactic methods and innovative technologies are discussed. Methods aimed at developing students’ speaking skills, explaining language rules and communicating are considered in detail. The role of the teacher and the importance of practical training in the process of teaching the mother tongue are emphasized. This article provides practical recommendations aimed at using effective methods in teaching the mother tongue.